Nuclear properties of a sample of nearby spiral galaxies from Hubble Space Telescope STIS imaging - Scarlata, C; Stiavelli, M; Hughes, M; Axon, D; Alonso-Herrero, A; Atkinson, J; Batcheldor, D; Binney, J; Capetti, A; Carollo, C; Dressel, L; Gerssen, J; et al. (2004)
We present surface photometry for the central regions of a sample of 48 spiral galaxies (mostly unbarred and barred of type Sbc or Sc) observed with the Space Telescope Imaging Spectrograph on board the Hubble Space Telescope. Surface brightness profiles (SBPs) were derived and modeled with a Nuker law. We also analyzed archival Wide Field Planetary Camera 2 images with a larger field of view, which are available for 18 galaxies in our sample. We modeled the extracted bulge SBPs with an exponential, an r1/4, or an r n profile. In agreement with previous studies, we find that bulges of Sbc galaxies fall into two categories: bulges well described by an exponential profile and those well described by an r1/4 profile. Only one galaxy requires the use of a more general Sérsic profile to properly describe the bulge. Nuclear photometrically distinct components are found in ∼55% of the galaxies. For those that we classify as star clusters on the basis of their resolved extent, we find absolute magnitudes that are brighter on average than those previously identified in spiral galaxies. This might be due to a bias in our sample toward star-forming galaxies, combined with a trend for star-forming galaxies to host brighter central clusters.